Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/slct.202102464
|View full text |Cite
|
Sign up to set email alerts
|

Hemilabile Properties of Sulfur‐Containing Cymantrene Derivatives

Abstract: Sulfur-containing cymantrene derivatives having one or two organometallic moieties were studied by NMR, IR, UV/Vis spectroscopic methods and CVA under irradiation conditions. Photolysis of compounds 1-3 leads to the formation of rare 4membered chelates 4, 5 and 8. In the presence of external ligand (L), dissociation of the MnÀ S bond occurred to form new dicarbonyl complexes with the MnÀ L bond, which demonstrates the hemilabile character of the chelates obtained. The results were confirmed by DFT calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…When changing n ‐donor solvent, which is able to form stable dicarbonyl intermolecular complexes with manganese, there is a sharp change in the UV‐vis spectra. Thus, the appearance of a weak band from the chelate complex is observed in DMF, which completely disappears after 10 min of thermal reaction, while a slight increase in the intensity of bands at 403 and 467 nm was recorded ( Figure S19 , Table 2) belonging to dicarbonyl complex with the Mn−DMF bond [13] . Upon irradiation, the light yellow solution immediately turns to red‐violet and after thermal reaction for 10 min changes to dark red.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…When changing n ‐donor solvent, which is able to form stable dicarbonyl intermolecular complexes with manganese, there is a sharp change in the UV‐vis spectra. Thus, the appearance of a weak band from the chelate complex is observed in DMF, which completely disappears after 10 min of thermal reaction, while a slight increase in the intensity of bands at 403 and 467 nm was recorded ( Figure S19 , Table 2) belonging to dicarbonyl complex with the Mn−DMF bond [13] . Upon irradiation, the light yellow solution immediately turns to red‐violet and after thermal reaction for 10 min changes to dark red.…”
Section: Resultsmentioning
confidence: 94%
“…Earlier we showed that when a solutions of cymantrene derivatives containing a substituent with electron‐donating fragments in the cyclopentadienyl ring are irradiated, CO is released and chelates are formed due to coordination of donor substituent fragments with a manganese atom [13] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations